Case Report: A case of carcinoma in situ of the bladder misdiagnosed as “chronic prostatitis” for a long time - Li, Chongbin; Zhu, Guiyun; Liu, Jianzhen; Li, Wei (Frontiers in Oncology, 2025)
BackgroundCarcinoma in situ of the bladder (CIS) has no specific clinical symptoms and is easily confused with inflammatory lesions of the bladder and urethra. It is usually not considered as the primary diagnosis and requires cystoscopic biopsy to confirm the diagnosis.Case presentationA 44-year-old male patient was diagnosed with chronic prostatitis due to “intermittent urinary frequency, dysuria, and urethral dribbling after defecation” and was treated with intermittent anti-infective and symptomatic therapy for 2 years, with symptoms recurring after discontinuing the medication. This patient underwent urine exfoliative cytology, which revealed exfoliated cancer cells, and proceeded to undergo cystoscopic biopsy, which did not reveal a pathologic basis for the cancer. The diagnosis of CIS was finally confirmed only after a diagnostic transurethral bladder mucosal electrodesiccation and pathologic examination. Bacillus Calmette-Guerin (BCG) bladder instillation was then performed for up to one and a half years, and the patient recovered.ConclusionBladder carcinoma in situ can present with urinary irritation symptoms similar to those of prostatitis and is therefore easily misdiagnosed as chronic prostatitis. It is recommended for patients with recurrent urinary frequency and dysuria as the main symptoms to undergo urine exfoliative cytology routinely if bladder tumor cannot be ruled out, and cystoscopy and biopsy should be performed if necessary to rule out CIS.